Doing research in sound design - Filimowicz, Michael (Sound design, 2022)
oing Research in Sound Design' gathers chapters on the wide range of research methodologies used in sound design. Editor Michael Filimowicz and a diverse group of contributors provide an overview of cross-disciplinary inquiry into sound design that transcends discursive and practical divides. The book covers Qualitative, Quantitative and Mixed Methods inquiry. For those new to sound design research, each chapter covers specific research methods that can be utilized directly in order to begin to integrate the methodology into their practice. More experienced researchers will find the scope of topics comprehensive and rich in ideas for new lines of inquiry. Students and teachers in sound design graduate programs, industry-based R&D experts, and audio professionals will find the volume to be a useful guide in developing their skills of inquiry into sound design for any particular application area"--